Cesarean Scar Pregnancy - A Rare Entity: Two Case reports - Mahato, Krishna; Bin, Yu (Birat Journal of Health Sciences, 2018)
Cesarean scar pregnancy is the implantation of an embryo within the mymometrium of prior cesarean scar which is a rare variant of ectopic pregnancy. Such implantation is life threatening leading to uterine rupture, extensive hemorrhage and serious maternal morbidity. Making an early diagnosis minimizes risk of such major hemorrhage thus preserving the uterus and further fertility. In this case report we discuss two different management options: ultrasound guided intragestational methotrexate injection with sac aspiration; and transvaginal hysterotomy considering the severity of presenting symptoms. Birat Journal of Health SciencesVol.2/No.3/Issue 4/Sep- Dec 2017, Page: 312-315